Biology and hatchery production of Chamelea gallina, Spisula solida and Venerupis corrugata, to support restocking and stock enhancement programs - Joaquim, Sandra (2015)
Despite the management measures introduced by the fisheries administration to adjust catches in order to ensure the conservation of the stocks, beds of Spisula solida, Chamelea gallina and Venerupis corrugata in Algarve show evident signs of depletion. To reverse this negative trends an active intervention may be necessary in order to restore the populations of those three species. The present thesis aimed to increase the knowledge on the biological processes and hatchery production of these species, to support future restocking/stock enhancement programs for wild stock management as well as to promote them as candidates for the shellfish aquaculture industry, encouraging the diversification in this activity. To achieve this objective, first the best founder population for aquaculture purposes was defined, for each species, in order to contribute to the conservation of the genetic variability of the target wild populations to be restocked. Thereafter, the optimal reproductive time of the species for artificial spawning induction in aquaculture was defined, based on the characterization of the reproductive cycle of the three studied species as well as its nutrient storage and exploitation strategy. Particular emphasis was given to the evaluation of any eventual relationships between the broodstock condition, oocytes quality and the larval viability of V. corrugata. The introduction of the new species C. gallina and S. solida in aquaculture was based on the existing Batch technology. However, the production of V. corrugata larvae was evaluated in an optimized laboratory-scale recirculating aquaculture system and compared with the traditional larval rearing system. Furthermore, a pilot experiment was designed to determine the feasibility of a stock-enhancement strategy, which consisted of transplanting individuals of S. solida from natural clam beds to a closed fishing area. Finally, the main results of this thesis encourage the diversification of aquaculture as a way to promote this activity and to support future restocking and stock enhancement programs for the target species.